The pharmacist's guide to drug eruptions and interactions - Litt, Jerome Z. (New York : Parthenon Publishing Group, 2001)
When a drug is administered and an adverse reaction occurs, the usual first port of call is the pharmacist. This guide allows the pharmacist to check the symptoms against the drug or identify the drug using the visible dermatological symptoms.
Introduction -- Classes of drugs -- Drug eruptions A-Z -- Descriptions of the 29 most common reaction patterns -- Drugs responsible for 95 different reaction patterns -- Index of trade and generic drug names.
Includes index.
Keywords: DERMATOPHARMACOLOGY